Research on strategies to enhance the effectiveness of financial information dissemination under the background of rural revitalization - Song Qinyu; Xi Zhuang (Association for Scientific Computing Electrical and Engineering (ASCEE), 2023)
This paper aims to put forward optimization strategies for the shortcomings of rural financial information dissemination, so as to improve the effectiveness of financial information dissemination in rural areas，so as to form a win-win situation of two-way financial information interaction between rural commercial banks and farmers, stimulating rural development. Under the background of rural revitalization, financial information dissemination can help financial enterprises establish brand image and promote financial products and services, which plays a significant role in getting through the